Mujeres y empleo extractivo en América Latina - De La Puente Burlando, Lorena (Pontificia Universidad Católica del Perú, 2017)
Women in Latin America tend to bear greatest negative costs due to extractive industries. Mining and hydrocarbons transform the livelihoods of local populations and also, gender roles that condition access to opportunities for men and women. However, gender roles do not only operate in extractive localities. fte same industry is mainly organized around a masculine culture that allows the marginalization of women as their work force. fte case of direct and indirect employment (formal, informal and illegal) is used to present a series of pending questions despite a context of little information available to understand gender impacts of the extractive industry.

Las mujeres en América Latina tienden a recibir mayores impactos negativos a causa de la industria extractiva. La minería y los hidrocarburos transforman los medios de vida de poblaciones locales y así también, los roles de género que condicionarían el mayor o menor acceso a oportunidades para hombres y mujeres. Sin embargo, los roles de género no sólo operan en localidades extractivas. La misma industria está mayoritariamente organizada en torno a una cultura masculina que permitiría la marginalización de las mujeres como su fuerza de trabajo. Se utiliza el caso del empleo directo e indirecto (tanto formal, informal e ilegal) para presentar una serie de preguntas pendientes ante un contexto de poca información sistemática disponible que comprenda los impactos de género de la industria extractiva en América Latina.
Women and Extractive industry jobs in Latin America
Keywords: Género; Mujeres; Minería; Petróleo; América Latina; https://purl.org/pe-repo/ocde/ford#5.06.00